COVID-19 Surveillance in Nowshera District, Pakistan - Khan, Hamzullah; Khalid, Muhammad; Akhtar, Mansoor; Haris, Muhammad (Central Asian Journal of Medical Sciences, 2020)
Objectives: To determine the frequency of 2019-nCoV infectivity and correlation of different variables with COVID-19 in the population of Nowshera District, Pakistan. Methods: In this prospective observational study, a total of 365 people suspected of having COVID-19 were included from February5, 2020, to April 25, 2020. Spearman's correlation was used to assess the correlation of various factors with COVID-19 test positivity. Results: The mean age and standard deviation of those assessed were 35 ± 16 years. Of the total, 264 (72.3%) were males and 101(27.7%) females. Of the 365 people suspected of having COVID-19, 148(40.54%) were selected for viral detection through PCR. Of 148, 41(27.70%) were COVID-19 positive. One hundred ninety-three (52.9%) of the participants had a history of contact with COVID-19 people suspected of having COVID-19, and 68 (18.6%) had a history of travel to an epidemic area with COVID-19. there was a positive correlation of PCR positivity of the participants with exposure (rs=0.23, p = 0.001) and travel history (rs = 0.12, p = 0.02), respectively. In gender groups, we observed a positive correlation of male gender with travel history (rs = 0.13, p = 0.02) and an increase in age (rs = 0.14, p = 0.006). Conclusions: The prevalence of infection was 27.70% using the PCR technique. Male gender and older age people were more at risk of developing COVID-19. There was a statistically significant correlation between viral infection and a history of travel to an epidemic area and close contact with COVID-19 patients.